Natural wood defect / Muhamad Amran Abdul Wahab - Abdul Wahab, Muhamad Amran (2009)
Wood is a basic sources for producing product based on wood and yet used in daily used. Besides, good condition of wood will produces better quality product. At the same time, the wood defect will effect the manufacturer because uncontrolled defects on wood. Example of wood defects are defects by nature, defects during drying process and defects during machining process. The best way to reduce the defects on wood are during drying the wood by following the proper drying schedule and the worker have to handle the machine carefully. This is important to get the better quality wood product in the market industry.